MODEL PEMBELAJARAN TWO-STAY TWO-STRAY BERBANTUANGEOGEBRA TERHADAP KEMAMPUAN KONEKSI MATEMATIS - riska ayu septianingrum; Eleonora dwi wahyuningsih; wikan budi utami (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2019)
The background of this research was based on students’ lack of mathematical connection ability in learning. The aim of this research was to determine students’ mathematical connection ability through Two-Stay Two-Stray learning model assisted by Geogebra application was better than that on cube and cuboid subject. The type of this research was Experimental and Design of Intact-Group Comparison Research. The sampling technique of this research used Cluster Random Sampling and students of grade VIII D, VIII E, VIII F in SMP Negeri 3 Slawi were chosen as the samples. The technique of collecting data used interview, documentation, and test. The result of this research showed that students’ mathematical connection ability through Two-Stay Two-Stray learning model assisted by Geogebra application was better than that without Geogebra application proven by the t-test.